2014
DOI: 10.1002/ejoc.201400082
|View full text |Cite
|
Sign up to set email alerts
|

A Commercially Available Tantalum Catalyst for the Highly Regioselective Intermolecular Hydroaminoalkylation of Styrenes

Abstract: The C–C bond‐forming catalytic hydroaminoalkylation of terminal alkenes or styrenes enables a direct and 100 % atom‐efficient synthesis of amines and can generally result in the formation of two regioisomers, the branched and the linear product. Herein, we report that high‐yielding intermolecular hydroaminoalkylation reactions of styrenes can be achieved with excellent regioselectivities in the presence of the commercially available homoleptic catalyst pentakis(dimethylamino)tantalum. In all cases, the branche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 35 publications
1
21
0
1
Order By: Relevance
“…For example, aminoalkene 15 bearing an electron‐donating para ‐methoxy‐substituent on the benzene ring gave the hydroaminoalkylation product 23 in 81% yield (Table 2, entry 8, 10 mol% 11 ) while the corresponding substrate 16 with the strongly electron‐withdrawing para ‐trifluoromethyl substituent did not react successfully (Table 2, entries 9 and 10). The latter result is in good agreement with the established fact that N ‐methyl‐ para ‐trifluoromethylaniline has already been identified as a poor substrate for intermolecular titanium‐ or tantalum‐catalyzed hydroaminoalkylation reactions 4m,6d,h. In this context, it is worth mentioning that aminoalkene 16 is not consumed under the reaction conditions and as a result, no formation of any additional products could be observed.…”
Section: Resultssupporting
confidence: 89%
“…For example, aminoalkene 15 bearing an electron‐donating para ‐methoxy‐substituent on the benzene ring gave the hydroaminoalkylation product 23 in 81% yield (Table 2, entry 8, 10 mol% 11 ) while the corresponding substrate 16 with the strongly electron‐withdrawing para ‐trifluoromethyl substituent did not react successfully (Table 2, entries 9 and 10). The latter result is in good agreement with the established fact that N ‐methyl‐ para ‐trifluoromethylaniline has already been identified as a poor substrate for intermolecular titanium‐ or tantalum‐catalyzed hydroaminoalkylation reactions 4m,6d,h. In this context, it is worth mentioning that aminoalkene 16 is not consumed under the reaction conditions and as a result, no formation of any additional products could be observed.…”
Section: Resultssupporting
confidence: 89%
“…6 It has been shown that N , N - 7 and N , O -chelated early transition metal complexes based on 2-pyridonate, 8 amidate, 9 phosphoramidate 10 and related ligands are active catalysts for the hydroaminoalkylation of olefins with a variety of primary and secondary amines (Scheme 1a). The reactions are widely considered to occur via the initial formation of metal amido intermediates through deprotonation of an N–H bond, 11 therefore limiting the starting materials to primary and secondary amines.…”
Section: Introductionmentioning
confidence: 99%
“…First of all, it can be seen from Table 1 that the mono(2,6‐diaminopyridinato) catalysts II and III do not favor the formation of the linear hydroaminoalkylation product 3b , which was the case with other aminopyridinato titanium catalysts 7g,7j. Although in comparison to Eisen's mono(formamidinate) complex, improved regioselectivities in favor of the branched hydroaminoalkylation product 3a (approximately 90:10) were observed with II and III it must be noted that much better selectivity in favor of 3a (≥ 98:2) has already been reported for the commercially available tantalum catalyst Ta(NMe 2 ) 5 5m…”
Section: Resultsmentioning
confidence: 66%
“…As can be seen from Table 2, a number of interesting hydroaminoalkylation reactions could be achieved in the presence of 10 mol % II at 140 °C. Although the yields obtained with the sterically demanding substrates N ‐methyl‐ ortho ‐toluidine or ortho ‐methylstyrene, which result in the formation of the products 7a / b and 8a / b were only poor to modest, it is worth mentioning that many established catalysts do not catalyze hydroaminoalkylation reactions of sterically demanding substrates at all 5m,7d,7j. Another drawback of many existing titanium catalysts is that hydroaminoalkylation reactions using halogenated substrates often proceed sluggishly 7d,7g,7h.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation